Analysis Application Compress Warm Water Edged Sponge in Lower Temperature Body on Patient Fever Typhoid - Alamsyah; Sulasri; Tut Handayani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Fever typhoid that is disease cystemia caused by tagged bacteria with fever long-lasting incident, body feel weak, sick heavy head, anorexia, and cough no productive. Typhoid fever causes a very high body temperature above the normal temperature and can damage the brain and other vital organs. The purpose of this study was to describe the application of a warm water tepid sponge compress to decrease body temperature in typhoid fever patients. The type of research that can be a type of descriptive research with a case study approach. From the results of the researcher's analysis, the warm compress of the tepid sponge was able to reduce the temperature in patients with typhoid fever because it was a direct block compress which was carried out at 5 points that had large blood vessels. This is evidenced by There was a decrease in body temperature before and after the application of a warm water tepid sponge compress on respondent An. M and An. N. The use of warm compress therapy with water tepid sponge is able to reduce the temperature so that it is used as one of the nurses' independent interventions in dealing with fever when arriving at the ER.